Exploring Relationships between Demersal Resources and Environmental Factors in the Ionian Sea (Central Mediterranean). (8th May 2012) - D'Onghia, G.; Giove, A.; Maiorano, P.; Carlucci, R.; Minerva, M.; Capezzuto, F.; Sion, L.; Tursi, A.
Abstract : The relationships between the abundance of demersal resources, environmental variables, and fishing pressure in the north-western Ionian Sea in the last two decades were evaluated. Data on the density collected during seventeen trawl surveys carried out from 1985 to 2005 were used. The following species were considered: Aristaeomorpha foliacea, Nephrops norvegicus, and Parapenaeus longirostris for crustaceans; Merluccius merluccius, Phycis blennoides, and Mullus barbatus for teleost fish. The recruitment index was also considered for N. norvegicus, P. longirostris, M. merluccius and Mullus barbatus . Six candidate models were evaluated for each density and recruitment data set either combining fishing effort with global (NAO) and regional (SST and precipitation) climatic indices, or models separately involving fishing effort, NAO, or regional climatic indices as the only predictive variable. Model selection was carried out using an information-theoretical approach that applies Akaike's Information Criterion (AIC). High changes over time were observed for the density data and recruitment indices in each species. Apart from hake abundance and recruitment data, for which a clear positive relationship with the NAO index alone was detected, the changes observed in the other species seem to be the consequence of the interaction between bottom-up effects linked to changes in physical environment and top-down ones due to the fishing pressure.